Decreased CDX2 Expression Adversely Effect On Prognosis Of Patients With Colorectal Cancer - Calik, Ilknur; Çalık, Muhammet; Özercan, Hanifi İbrahim; Dagli, Adile Ferda; Artaş, Gökhan; Türken, Gülistan; Sarıkaya, Burcu (My University, 2020)
Objective: Since colorectal cancers (CRC) are tumors with heterogeneous biological behavior, prediction of theirprognosis remains challenging. Caudal-related homeobox gene 2 (CDX2), which has important roles in the developmentand maintenance of intestines, is thought to have tumor suppressing effect on CRCs. The aim of this study was toinvestigate the prognostic significance of decreased-CDX2 expression.Method: This retrospective study included 224 patients diagnosed with CRC between 2009 and 2014. Paraffinized blocksof these patients were stained with CDX2 immunohistochemically and evaluated semiquantitatively.Results: Only 35 (15.6%) of 224 patients had low-CDX2 expression. Decrease in CDX2 expression was closely associatedwith classical prognostic parameters such as histopathologic type, histologic grade, lymph node metastasis, distantmetastasis, and TNM stage. Patients with decreased-CDX2 expression had more lymph node metastasis (p=0.013) andadvanced TNM stage (p=0.004) than those without decreased-expression. The mean survival was 53.0±0.89 months. Coxregression analysis showed that decreased-CDX2 expression was significantly related with overall survival (Univariateanalysis; hazard ratio: 0.09, 95% confidence interval: 0.05-0.16; p<0.001; Multivariate analysis; hazard ratio: 0.24, 95%confidence interval: 0.13-0.48; p<0.001) and disease-free survival (Univariate analysis; hazard ratio: 0.80, 95% confidenceinterval: 0.05-0.13; p<0.001; Multivariate analysis; hazard ratio: 0.15, 95% confidence interval: 0.08-0.25; p<0.001).Conclusion: Decreased CDX2 expression is significantly related with worse biological features and can be used as anindependent prognostic biomarker in patients with CRCs.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Onkoloji